ABOUT THE PREREQUISITE SITUATION IN THE CASE OF THE OFFENSE OF MISAPPROPRIATION OF A WORK - Ciprian Raul ROMIȚAN (Challenges of the Knowledge Society)
Article 197(1) of Law no. 8/1996 on copyright and related rights, republished, criminally sanctions the appropriation of a work or part of a work by a person who has not contributed to the creation of that work and who presents it as his/her own creation. The act of appropriating a work or part of a work can be done in various ways, such as: publishing works under one's own name, as if it were made by the author, signing an intellectual creation, as co-author, in the literary, scientific, musical, artistic or fine art field without having any contribution to its creation, etc. Analysis of the legal text shows that the material element of this offense consists of two cumulative actions, namely the act of appropriating, without right, in whole or in part, the work of another author and the act of presenting it as one's own intellectual creation. At the same time, the analysis of the author of this study shows that in order to be able to prove the commission of this offense it is necessary that the appropriation is followed by the presentation of the work as one's own creation. It should be emphasised that in the absence of the action of presentation, it cannot be held that the offense provided for and punished by art. 197(1) of Law 8/1996 on copyright and related rights, republished, has been committed.